Study of Microstructural and Corrosion Properties of Aluminium Alloy 7075 after Plasma Nitriding - Haerul Ahmadi; Rizky Abdul Aziz; Suprapto Suprapto; Tjipto Sujitno; Sophie Hapsari (Jurnal Sains Materi Indonesia, 2019)
Plasma nitriding is a treatment process of metals by depositing nitrogen into metal that considered to be nitrided by mean of increasing the mechanical, physical, and chemical properties of the metal. This treatment will form a hard layer compund of Al-N on the surface of the sample. In this study, aluminium alloy 7075 was nitrided which the application of it to structural part of aircraft makes it vulnarable to not only corrosion and wear attack but also decreasing the hardness of the material. One method to overcome these issues is plasma nitriding. The purpose of of this research is to do the characterizations of plasma nitrided aluminium alloy 7075 regarding its microstructure, mechanical, and chemical properties. The characterizations that had been done were microhardness Vickers testing, SEM-EDX, and electrochemical corrosion testing Potensiostat. The hardness of the sample increased 55% from 75,88 VHN (raw material) to 117,68 VHN (at optimum parameter). The depth of the white layer of plasma nitriding is approximately 6 µm, while the EDX result reported carbon, oxygen, and nitrogen presence. Corrosion testing showed that the highest corrosion rate is on the raw material, 0,15393 mpy. While the optimum one is 0,07184 mpy.